Fungsi Laten dan Fungsi Manifes Wirausaha Perempuan terhadap Pembangunan Ekonomi di Kota Sabang - Chadijah, Devi Intan; Juraida, Irma; Yana, Rahmah Husna; Yulianda, riki (Universitas Muhammadiyah Tapanuli Selatan, 2024)
This research aims to determine the manifest and latent functions of women entrepreneurs and what impacts they have on economic development in Sabang City. This research uses a qualitative method with a descriptive approach. Based on the analysis results, it can be concluded that the latent function and manifest function always appear in every condition. This can be seen from (1) Difficult economic factors have proven to encourage female entrepreneurs to get involved in the business world. For the government this is a desired function (manifest function). However, for women's personal lives, this is an undesirable function because it causes women's duties and responsibilities as wives and mothers to increase. (2) Environmental factors, the support of the women's entrepreneurial community is also a strength in women's entrepreneurship. This is certainly a manifest function for economic development in Sabang City. However, it is a latent function for the individual woman herself due to (3) Family Factors, women who are entrepreneurs are proven to be more productive, can also make the family prosperous and increase regional income (manifest function). Meanwhile, in terms of parenting, it becomes an obstacle due to dual roles. Thus, these three factors are a manifestation of a social system that is considered functional for a group, but this can also be non-functional for other groups.